2020
DOI: 10.1186/s12964-020-00610-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Follistatin like 1 ameliorates liver fibrosis induced by carbon tetrachloride through TGF-β1-miR29a in mice

Abstract: Background Hepatic fibrosis is a pathological response of the liver to a variety of chronic stimuli. Hepatic stellate cells (HSCs) are the major source of myofibroblasts in the liver. Follistatin like 1 (Fstl1) is a secreted glycoprotein induced by transforming growth factor-β1 (TGF-β1). However, the precise functions and regulation mechanisms of Fstl1 in liver fibrogenesis remains unclear. Methods Hepatic stellate cell (HSC) line LX-2 stimulated by TGF-β1, primary culture of mouse HSCs and a model of liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
0
15
1
Order By: Relevance
“…Inhibition of follistatin‐like 1 significantly inhibits TGF‐β1‐stimulated cell migration and ECM accumulation; follistatin‐like 1 is thus a therapeutic target for the treatment of liver fibrosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of follistatin‐like 1 significantly inhibits TGF‐β1‐stimulated cell migration and ECM accumulation; follistatin‐like 1 is thus a therapeutic target for the treatment of liver fibrosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, others have already shown that rituximab may induce Ccl20 expression in human blood [39]. Furthermore, the expression of Fst is associated with liver fibrosis [40,41], while the downregulation of Clstn2 was observed in progressive RA [42]. At this point, it is reasonable to speculate about a connection between the cytokine release syndrome and rituximab, which is certainly known in certain circumstances [43].…”
Section: Discussionmentioning
confidence: 89%
“…Fstl1 binds to TGF-β1 and negatively regulates TGF-β1 signaling in lung development. Interestingly, Fstl1 neutralizing antibody attenuates CCL4 induced liver fibrosis [ 136 ]. Further studies are required to reconcile results from developmental and disease models.…”
Section: Hepatic Mapk Mediates Progression Of Nafl/nashmentioning
confidence: 99%